Integration of mechanistic and pharmacokinetic information to derive oral reference dose and margin‐of‐exposure values for hexavalent chromium. Issue 3 (24th October 2017) - Thompson, Chad M.; Kirman, Christopher R.; Hays, Sean M.; Suh, Mina; Harvey, Seneca E.; Proctor, Deborah M.; Rager, Julia E.; Haws, Laurie C.; Harris, Mark A.
Abstract: The current US Environmental Protection Agency (EPA) reference dose (RfD) for oral exposure to chromium, 0.003 mg kg −1 day −1, is based on a no‐observable‐adverse‐effect‐level from a 1958 bioassay of rats exposed to ≤25 ppm hexavalent chromium [Cr(VI)] in drinking water. EPA characterizes the confidence in this RfD as "low." A more recent cancer bioassay indicates that Cr(VI) in drinking water is carcinogenic to mice at ≥30 ppm. To assess whether the existing RfD is health protective, neoplastic and non‐neoplastic lesions from the 2 year cancer bioassay were modeled in a three‐step process. First, a rodent physiological‐based pharmacokinetic (PBPK) model was used to estimate internal dose metrics relevant to each lesion. Second, benchmark dose modeling was conducted on each lesion using the internal dose metrics. Third, a human PBPK model was used to estimate the daily mg kg −1 dose that would produce the same internal dose metric in both normal and susceptible humans. Mechanistic research into the mode of action for Cr(VI)‐induced intestinal tumors in mice supports a threshold mechanism involving intestinal wounding and chronic regenerative hyperplasia. As such, an RfD was developed using incidence data for the precursor lesion diffuse epithelial hyperplasia. This RfD was compared to RfDs for other non‐cancer endpoints; all RfD values ranged 0.003–0.02 mg kg −1 day −1 . The lowest of these values is identical to EPA's existing RfD value. Although the RfD value remains 0.003 mg kg −1 day −1, the confidence is greatly improved due to the use of a 2‐year bioassay, mechanistic data, PBPK models and benchmark dose modeling. Abstract : The current US Environmental Protection Agency reference dose (RfD) for chromium (0.003 mg kg −1 day −1 ) is based on a 1958 study. A recent 2 year bioassay found that hexavalent chromium [Cr(VI)] in drinking water is carcinogenic to rodents. To assess whether the current RfD is health protective, effects in the recent bioassay were analyzed using physiological‐based pharmacokinetic and benchmark dose modeling. Mechanistic data supported development of RfDs for cancer and non‐cancer effects. Calculated RfDs ranged 0.003–0.02 mg kg −1 day −1, indicating that the existing RfD is protective of Cr(VI)‐induced non‐cancer and cancer effects.